Comparison of cost-effectiveness of implantable cardioverter defibrillator therapy in patients for primary prevention in Latin America: an analysis using the Improve SCA study. (1st January 2021) - Higuera, Lucas; Holbrook, Reece; Wherry, Kael; Rodriguez, Diego A.; Cuesta, Alejandro; Valencia, Juan; Arcos, Julián; López Gómez, Agustín
Abstract: Objective: The mortality benefit of implantable cardioverter defibrillators (ICDs) for primary prevention (PP) of sudden cardiac arrest (SCA) has been well-established, but ICD therapy remains globally underutilized. The results of the Improve SCA study showed a 49% relative risk reduction in all-cause mortality among ICD patients with 1.5 primary prevention (1.5PP) characteristics (patients with one or more risk factors, p < 0.0001). We evaluated the cost-effectiveness of ICD compared to no ICD therapy among patients with 1.5PP characteristics in three Latin American countries and analyzed the factors involved in cost-effectiveness. Methods: We used a published Markov model that compares costs and outcomes of ICD to no ICD therapy from local payers' perspective and included country-specific and disease-specific inputs from the Improve SCA study and current literature. We used WHO-recommended willingness-to-pay (WTP) thresholds to assess cost-effectiveness and compared model outcomes between countries. Results: Incremental costs per QALY (quality-adjusted life year) saved by ICD compared to no ICD therapy are Colombian Pesos COP46, 729, 026 in Colombia, Mexican Pesos MXN246, 016 in Mexico, and Uruguayan Pesos UYU1, 213, 614 in Uruguay in the base case scenario; all three figures are between 1–3-times GDP per capita for each country. One-way and probabilistic sensitivity analyses confirm the base case scenario results. Non-cardiac accumulated deaths are lower in Mexico, resulting in a comparatively increased cost-effective ICD therapy. Limitations: The Improve SCA study was not randomized, so clinical results could be biased; however, measures were taken to reduce this bias. Costs and benefits were modelled beyond the timeline of direct observation in the Improve SCA study. Conclusions: ICD therapy is cost-effective in Mexico and Uruguay and potentially cost-effective in Colombia for a 1.5PP population. Variability in ICER estimates by country can be explained by differences in non-cardiac deaths and cost inputs.